2021
DOI: 10.1186/s13287-021-02231-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glioblastoma stem cells in cancer therapeutic resistance: a perspective on antineoplastic agents from natural sources and chemical derivatives

Abstract: Glioblastoma (GBM) is the highest-grade form of glioma, as well as one of the most aggressive types of cancer, exhibiting rapid cellular growth and highly invasive behavior. Despite significant advances in diagnosis and therapy in recent decades, the outcomes for high-grade gliomas (WHO grades III-IV) remain unfavorable, with a median overall survival time of 15–18 months. The concept of cancer stem cells (CSCs) has emerged and provided new insight into GBM resistance and management. CSCs can self-renew and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 223 publications
1
83
0
Order By: Relevance
“…Spheroid formation has been proposed as a robust, independent predictor of glioma tumour progression 6 and the presence of glioma stem cells (GSCs), which are enriched in spheroids, may be connected to the drug resistance of GBM due to their enhanced antioxidant defence 7 and elevated DNA repair capacity. 8 In this report we firstly compared the growth inhibitory capacity of SFN from SFX-01 versus reference SFN using a series of tumour cell lines. Secondly we compared their effects against four low-passage GBM cell lines that had been generated and grown under physiological oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Spheroid formation has been proposed as a robust, independent predictor of glioma tumour progression 6 and the presence of glioma stem cells (GSCs), which are enriched in spheroids, may be connected to the drug resistance of GBM due to their enhanced antioxidant defence 7 and elevated DNA repair capacity. 8 In this report we firstly compared the growth inhibitory capacity of SFN from SFX-01 versus reference SFN using a series of tumour cell lines. Secondly we compared their effects against four low-passage GBM cell lines that had been generated and grown under physiological oxygen conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The first accepted surface marker for glioblastoma stem cells was CD133 [141] that it allows the subdivision of stem cells into two groups of CD133 + or cancer stem cells and CD133 − or non-cancer stem cells [142]. Other markers expressed in glioblastoma stem cells are CD15, CD184, CD44, A2B5, CD90, SOX2, OCT-4, SALL4, NANOG, ALDH1, L1CAM, KLF4, and so on [76,[143][144][145][146][147][148][149][150][151][152][153]. Some studies have reported that resveratrol is able to target glioma glioblastoma stem cells through various molecular pathways involved in self-renewal and several stem cell markers.…”
Section: Therapeutic Potentials Of Resveratrol In Glioblastoma Chemotherapymentioning
confidence: 99%
“…However, long-term TMZ administration typically results in resistance, limiting its efficacy (15). The stem-like characteristics of GBM cells are primarily responsible for its resistance to chemotherapy, immunotherapy and radiation (16). Therefore, adjuvant therapy, such as chemotherapy or immunotherapy, may be applied to overcome drug resistance and to improve the survival rates of patients with GBM (17).…”
Section: Introductionmentioning
confidence: 99%